Synthesis of hierarchical mesoporous Ln2Ti2O7 (Ln = Y, Tb–Yb) pyrochlores and uranyl sorption properties. (20th June 2022) - Kong, Linggen; Karatchevtseva, Inna; Wei, Tao; Scales, Nicholas
Highlights: · A method is developed to synthesize crystalline metal oxides with a ternary composition and hierarchical mesopore structure. · Phase pure Ln2 Ti2 O7 (Ln = Y, Tb–Yb) pyrochlores are produced with high specific surface area (∼ 70 m 2 ·g –1 ) and pore volume (∼ 0.35 cm 3 ·g –1 ), and significant portion of mesopores (10–40 nm). · Good uranyl adsorption capacity (U uptake ∼ 60 mg·g −1 ) and fast adsorption kinetics are observed due to the unique morphology structure of the material. Abstract: Mesoporous structured metal oxides exhibit many active applications. However, the synthesis of crystalline metal oxides with a ternary composition while maintaining satisfactory pore features is challenging. Typically, high temperatures are required which inhibit control of pore structure properties including surface area, pore volume, and pore size. Herein, the synthesis of ternary metal oxides Ln 2 Ti2 O7 possessing pyrochlore crystal structure is achieved using a novel technique which combines 'soft' and hard colloid templating strategies. The formed materials are of submicron size and composed of ∼ 25–30 nm product 'building blocks' with good chemical and phase stability. The polycrystalline powders have a high specific surface area (up to 70 m 2 ·g –1 ) and pore volume (∼ 0.35 cm 3 ·g –1 ) which result in a good adsorption capacity (U uptake closing to 60 mg·g –1 ). Remarkably, the material exhibits a significant portion of mesopores (mainly 10–40 nm) which facilitate fast adsorption of the cations due to high accessibility. The synthetic methodology described herein produces highly homogenous powders and can be applied to other compositions and structures. Graphical abstract: Image, graphical abstract